Consistent Monthly Reproduction and Completion of a Brooding Coral Life Cycle through Ex Situ Culture - Kwok-Wai Lam; Crystal J. McRae; Xuan-Ci Zhang; Zong-Min Ye; Yu-Ting Qiu; Ming-Qi Jiang; Ting-Hui Cheng; Guanyan Keelung Chen; Tung-Yung Fan (Diversity, 2023)
The continuing impact of local and global stressors on coral reefs worldwide is prompting the exploration of novel approaches aimed at mitigating and improving the bleak future projections for corals. Ex situ aquaculture has the potential to provide a standardized supply of source corals to support active intervention-based research endeavours as well as complementary reef restoration initiatives. To effectively achieve this supply of coral, however, ex situ aquaculture systems need to be able to efficiently maintain reproducing colonies, and have the capacity to support each coral life stage. We monitored the monthly reproduction of the brooding coral, Pocillopora acuta, for one year in two distinct aquaculture systems: a natural seawater-supplied flow-through system (FTS) and an artificial seawater-supplied recirculating aquaculture system (RAS). The coral colonies in both aquaculture systems showed relatively consistent reproduction over time (on average > 70% of all colonies reproducing each month) and maintained natural diel reproduction patterns even after 1 year of ex situ culture. Coral colony reproductive output and timing (i.e., lunar day of release) differed between aquaculture systems in some, but not all, seasons. Planulae released from colonies settled and grew to reproductive size after ~16 months of culture, resulting in the ex situ production of an F2 generation of a brooding coral within two distinct aquaculture systems. This demonstrated that the use of ex situ aquaculture could be directly applied to research, restoration, and conservation aimed at mitigating coral decline in a future marred by climate change and local impacts.